THE CORRELATION BETWEEN THE SINGING METHOD AND STUDENTS’ UNDERSTANDING IN BALAGHAH LEARNING - Khairun Nisa; M. Rohiq; Neldi Harianto; Amami Shofiya Al Qorin (Yayasan Adra Karima Hubbi, 2026)
This research was motivated by the low level of understanding among some students in balaghah, which is often considered difficult because it involves abstract linguistic concepts and rules. In the learning process, a method is needed to improve students’ interest and understanding of the material being studied. One of the methods used is the singing method, namely the delivery of material through rhythm or songs, making it easier to understand and remember. This research aims to determine the correlation between the singing method and students’ understanding of balaghah learning at the Al-Baqiyatush Shalihat Islamic Boarding School, Kuala Tungkal. This research used a non-experimental quantitative approach with a correlational research design. The data were obtained through questionnaires, tests, observation, and documentation. The data analysis technique used Product-Moment correlation to assess the relationship between the singing method variable and students’ understanding. The results of the research showed that the implementation of the singing method in balaghah learning was in the good category, while students’ understanding was in the fairly good category. Correlation analysis revealed a positive correlation between the singing method and students’ understanding of balaghah learning. These findings indicate that the singing method can help create a more active and enjoyable learning atmosphere and facilitate students' understanding of balaghah material. Thus, the singing method can serve as an alternative learning approach to improve students’ understanding of balaghah.